Mortality Among Patients Discharged From an Acute Psychiatric Department: A 5-Year Prospective Study - Prestmo, Astrid; Høyen, Karina; Vaaler, Arne Einar; Torgersen, Terje; Drange, Ole Kristian (Frontiers in Psychiatry, 2020)
The primary aim of the study was to explore the post discharge standardized mortality ratio of patients from an acute psychiatric department in Norway. The secondary aims were to explore if the standardized mortality ratio is still increasing and to examine the causes of death in the defined population. We conducted a 5-year prospective study among patients admitted to an acute psychiatric department with catchment area responsibilities. A total of 380 patients were included in the study, and the number and causes of deaths were obtained from the Norwegian Cause of Death Registry. Excess mortality was found for the patient group. The standardized mortality ratio for all causes of death was 6.7 (95% CI 4.6-8.8). The study finds an increased standardized mortality ratio relative to a previous corresponding study in Norway, and the suicide risk is especially elevated the first two years after discharge.